Analysis of functionality free CASE-tools databases design - A. V. Gavrilov (Открытое образование (Москва), 2016)
The introduction in the educational process of database design CASEtechnologies requires the institution of significant costs for the purchase of software. A possible solution could be the use of free software peers. At the same time this kind of substitution should be based on even-com representation of the functional characteristics and features of operation of these programs. The purpose of the article – a review of the free and non-profi t CASE-tools database design, as well as their classifi cation on the basis of the analysis functionality. When writing this article were used materials from the offi cial websites of the tool developers. Evaluation of the functional characteristics of CASEtools for database design made exclusively empirically with the direct work with software products. Analysis functionality of tools allow you to distinguish the two categories CASE-tools database design. The first category includes systems with a basic set of features and tools. The most important basic functions of these systems are: management connections to database servers, visual tools to create and modify database objects (tables, views, triggers, procedures), the ability to enter and edit data in table mode, user and privilege management tools, editor SQL-code, means export/import data. CASE-system related to the first category can be used to design and develop simple databases, data management, as well as a means of administration server database. A distinctive feature of the second category of CASE-tools for database design (full-featured systems) is the presence of visual designer, allowing to carry out the construction of the database model and automatic creation of the database on the server based on this model. CASE-system related to this categories can be used for the design and development of databases of any structural complexity, as well as a database server administration tool. The article concluded that the qualitative training of specialists in the field of information technology is impossible without an understanding of the students of the principles of construction of the database, practical development of modern methods of design and development database. Instrumental basis of database design information technology are modern CASE-tools. Today, on the software market presented a large number of commercial CASE-systems database design, which differ in their characteristics. The limiting factor is widely used in the Russian universities CASE-technologies database design is the high cost of the software. We have in its review of the free and non-profi t CASE-tools database design, their systematization to help teachers and students in the choice of available tools design and development database.